2004
DOI: 10.1002/gea.20035
|View full text |Cite
|
Sign up to set email alerts
|

Using sulfur isotopes to determine the sources of vermillion in ancient burial mounds in Japan

Abstract: This study represents an attempt to determine the sources of vermillion found in ancient Japanese burial mounds of the 1st-6th centuries A.D., by comparing their ratios of sulfur isotopes with those of cinnabar ore samples collected in Japan and China. Cinnabar ore samples were taken from three mines in central Japan (Niu in Mie, Yamato in Nara, and Sui in Tokushima prefectures), and from Wanshan in China, where mining activity has been recorded back to the 6th century A.D. and earlier. When the ratios of 34 S… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
16
0
1

Year Published

2006
2006
2021
2021

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(17 citation statements)
references
References 5 publications
0
16
0
1
Order By: Relevance
“…The localities of the deposits from where the determined cinnabar was collected are referred to Figure 1 and Table 1. value of cinnabar from Furumiya is -6.1 ‰. Minami et al (2005) reported that the δ 34 S values of cinnabar from the Suii deposit are -2.4±1.4 ‰. The δ 34 S values of cinnabar from the Wake deposit, western Honshu, Inner Zone of Southwest Japan arc, associated with Uppermost Cretaceous hydrothermal alteration and volcanic rocks is -6.2 ‰.…”
Section: Sulfur Isotope Of Hg Deposits In Japanmentioning
confidence: 97%
See 2 more Smart Citations
“…The localities of the deposits from where the determined cinnabar was collected are referred to Figure 1 and Table 1. value of cinnabar from Furumiya is -6.1 ‰. Minami et al (2005) reported that the δ 34 S values of cinnabar from the Suii deposit are -2.4±1.4 ‰. The δ 34 S values of cinnabar from the Wake deposit, western Honshu, Inner Zone of Southwest Japan arc, associated with Uppermost Cretaceous hydrothermal alteration and volcanic rocks is -6.2 ‰.…”
Section: Sulfur Isotope Of Hg Deposits In Japanmentioning
confidence: 97%
“…The δ 34 S value of cinnabar from the Chihaya deposit is +1.3 ‰. Minami et al (2005) reported that the δ 34 S values of cinnabar from the Yamato-suigin deposit and from the Niu deposit are -2.1 ±1.6 ‰ and 7.3±1.9 ‰, respectively. Shimazaki (1985) reported the δ 34 S value of composite ore (mainly cinnabar with small amounts of pyrite and marcasite) from the Yamato-suigin deposit to be -4.6 ‰.…”
Section: Sulfur Isotope Of Hg Deposits In Japanmentioning
confidence: 97%
See 1 more Smart Citation
“…For this purpose, we first collected cinnabar ore from mines in Japan and China recorded in Japanese and Chinese histories and found that the ratio of sulfur isotopes was different between Japanese and Chinese ore. [3][4][5][6] Ishihara et al 7) measured the sulfur isotope ratio in sulfur component ore of deposits from the latter half of the Cenozoic period from Chubu to Kyushu districts in Japan, and they reported that the sulfur isotope ratio of the sulfur component ore depended on the region, not on both the mineral and deposit. We then tried to discover the original source of vermilion used in the remains by using the sulfur isotope ratio in vermilion.…”
Section: Introductionmentioning
confidence: 99%
“…El cinabrio fue ampliamente utilizado desde la prehistoria en diferentes lugares del mundo, tales como Ydria en la ex Yugoslavia, Essex en Inglaterra, Dordoña en Francia, Chavín de Huantar en Perú (Forbes 1965-67;Shepherd 1980), Japón (Minami 2005) y España (Domínguez-Bella 2010, 2011Martín-Gil et al 1994).…”
unclassified